2019
DOI: 10.3889/oamjms.2019.579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shear-Bond-Strength of Dental Self-Adhering Flowable Resin-Composite versus Total-Etch One to Enamel and Dentin Surfaces: An In-Vitro Study

Abstract: AIM: This study aimed to assess the shear bond strength of a self-adhering flowable resin composite versus a total-etch one to different surfaces of permanent-molars. MATERIAL AND METHODS: Thirty-six sound human permanent molars were used. The teeth were embedded in acrylic blocks, such that their buccal surfaces were shown. The teeth were divided into three groups: Group I: Uncut-Enamel, Group II: Cut-enamel-surfaces with minimal-grinding and Group III: dentin-surfaces. Half of the teeth in each group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 19 publications
1
23
0
10
Order By: Relevance
“…These findings agree with previous work, who suggested that changes in the filler content may result in higher SBS (Kucukyilmaz & Savas, 2015; Singh, Kaur, & Kapoor, 2019). The shear bond values presented by the experimental formulations were similar or higher than shear bond values reported in the literature (Abdelraouf, Mohammed, & Abdelgawad, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…These findings agree with previous work, who suggested that changes in the filler content may result in higher SBS (Kucukyilmaz & Savas, 2015; Singh, Kaur, & Kapoor, 2019). The shear bond values presented by the experimental formulations were similar or higher than shear bond values reported in the literature (Abdelraouf, Mohammed, & Abdelgawad, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, given all the consequences to the exposure of the collagen matrix by phosphoric-acid etching, this approach can be considered as an aggressive procedure to the dentinal structure. 3,6,7,9,10 The self-etch adhesive system had the second-highest bond value between the tested groups, with no statistically significant with the etch and rinse group. Its bonding property depends on a functional acid monomer, 10-methachryloylozydecyl dihydrogen phosphate (MDP) that interacts with the hydroxyapatite in the tooth.…”
Section: Discussionmentioning
confidence: 87%
“…The acidic monomer in the self-adherent composite, glycerolphosphate dimethacrylate (GPDM), is responsible for surface etching and chemical bond to calcium ions from the tooth by the acidic phosphate action, while the methacrylate component holds the polymerisation process and support the micromechanical interlocking mechanism between the monomer and demineralized collagen fibril of the dentin. 6,7,8 As stated before, that bonding to enamel and dentin have different challenges, a study on the self-adherent resin composite bonding ability showed that self-adherent flowable resincomposite had lower bond strength to enamel and dentin than the total-etch (etch and rinse) system. 7 In line with the mentioned results, bonding effectiveness of the self-adherent composite resin was also underscored to the self-etch adhesive system followed by the application of a flowable composite.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[ 4 ] However, various authors have reported relatively low bond strength values of SAC to dental hard tissues, thus necessitating an alteration in the bonding approach. [ 5 6 7 ] Restorative demands frequently present with clinical situations requiring bonding to intact, altered, or prepared enamel surfaces, which might bond differently with adhesive resins. Considering the limited information on bonding of SAC to enamel available in literature, this study was undertaken to evaluate the effect of mechanical alteration of enamel surface on shear bond strength of self-adhering composites utilizing different adhesive modalities.…”
Section: Introductionmentioning
confidence: 99%